Microstructure Evolution and Mechanical Properties of B4C-Reinforced TC11 + xFe Composites Fabricated by HIP - Shenwei Qian; Nan Wang; Feng Chen; Yangyang Sun; Jiong Zhao; Hui Chang; Liang Feng; Lian Zhou (Metals)
The present study involved (TiB + TiC)/TC11 (Ti-6.5Al-3.5Mo-1.2Zr-0.3Si) + xFe titanium matrix composites (TMCs) reinforced by in situ TiB whiskers and TiC particles fabricated by hot isostatic pressing. Microstructure observation reveals a substantial distribution of in situ reinforcements, which form a network-reinforced structure at the prior particle boundaries of the TC11 matrix. The micro–nanoscale TiB whiskers and TiC particles within and surrounding this network serve as effective dislocation pinning. The enhancement of mechanical properties can be attributed to load-bearing strengthening, fine-grain strengthening, and dislocation strengthening. The hardness and compressive strengths were investigated through mechanical properties testing. The hardness increased by 19.4% (2 wt% B4C-reinforced composites) compared with TC11 alloy. However, the addition of 2 wt% Fe at the same B4C level (2 wt% B4C + 2 wt% Fe-reinforced composites) resulted in a significant increase in hardness by 37.5% and 15.2% in compressive strengths of TMC and can be attributed to the solid solution strengthening effect and higher dislocation density provided by the addition of Fe. In addition, the optimal overall properties can be achieved by strictly regulating the addition ratio of 2 wt% Fe and 1 wt% B4C, allowing for a compressive strength of 2301 MPa while still maintaining a compressive strain of 24.6%.